Hippocampal beta oscillations predict mouse object‐location associative memory performance. Issue 5 (8th February 2021) - Iwasaki, Satoshi; Sasaki, Takuya; Ikegaya, Yuji
Abstract: Memorizing the locations of environmental cues is crucial for survival and depends on the hippocampus. We recorded local field potentials (LFPs) from the hippocampus of freely moving mice during an object location task. The power of beta‐band (23–30 Hz) oscillations increased immediately before approaching objects in a memory‐encoding phase. The exploration‐induced beta oscillations gradually decreased during the memory‐encoding session. Mice that exhibited stronger beta oscillation power exhibited better performance in the subsequent memory‐retrieval test. These results suggest that beta oscillations in the hippocampal CA1 region are involved in the memory encoding of object‐location associations.